Analysis of the Effectiveness of Lecture and Singing Methods in Improving Oral Health Knowledge Among Elementary School Students at SDIT Lantabur in Pagar Alam City in 2025 - Desinta Nataleni; Tuti Rohani; Yunita Theresiana; Hartian Pansori; Firman Bintara (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Dental and oral health problems among elementary school-aged children remain high and are influenced by a lack of knowledge about how to maintain dental and oral hygiene. Health education is a preventive measure aimed at improving children’s knowledge, with lectures and singing serving as educational approaches that are easy to implement. This study aims to analyze the effectiveness of lectures and singing in improving oral health knowledge among students at SDIT Lantabur in Pagar Alam City in 2025. This study employed a mixed-methods design with a quasi-experimental two-group pretest–posttest design. The sample consisted of 82 first-grade students divided into two groups, each comprising 41 students who received health education using the lecture method and the singing method, respectively. Data were collected using questionnaires administered before and after the intervention and were analyzed using univariate and bivariate analyses. The results of the study show that before the lecture-based instruction, most students had insufficient knowledge (82.9%), and after the instruction, this increased to adequate knowledge (51.2%). Before the singing-based instruction, most students had insufficient knowledge (61%), and after the instruction, this increased to good knowledge (73.2%). Statistical tests showed that the lecture method was effective in improving students’ knowledge (p-value = 0.000) and the singing method was also effective (p-value = 0.000). The singing method proved to be more effective than the lecture method. The conclusion of this study is that the singing method is more effective in improving elementary school students’ knowledge of oral health.